Use of locally available ingredients to produce small ruminant feed in pellet form in Tunisia - CGIAR Research Program on Livestock (2020)
Imported small scale pelleting machines have been tested to produce pellets for small and large ruminants, using locally available ingredients such as wheat bran, barley grains, olive cake, and faba beans.